Geographic factors and geocryological activity in Livingston Island, Antarctic. Preliminary results - Vieira, Gonçalo (2019)
The study presents results from the geomorphological mapping of geocryological phenomena on the northwest sector of Hurd Peninsula, Livingston Island, including frost- shattered debris, talus slopes, stonebanked lobes, rockglaciers and patterned ground. Results are integrated in a GIS and compared to data on altitude, slope angle, aspect and calculated summer net radiation. They show a generally poor influence of the studied climate-related variables, a fact that may be related to the particular climatic characteristics [...]